2017
DOI: 10.3892/ijmm.2017.3174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNA expression profiling in human umbilical vein endothelial cells affected by heat stress

Abstract: To investigate the regulation of endothelial cell (EC) microRNAs (miRNAs) altered by heat stress, miRNA microarrays and bioinformatics methods were used to determine changes in miRNA profiles and the pathophysiological characteristics of differentially expressed miRNAs. A total of 31 differentially expressed miRNAs were identified, including 20 downregulated and 11 upregulated miRNAs. Gene Ontology (GO) enrichment analysis revealed that the validated targets of the differentially expressed miRNAs were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Based on previous miRNA microarray analysis, miR-3613-3p expression levels were decreased in HUVECs under heat stress (19). To confirm the downregulation of miR-3613-3p in heat-treated cells, miR-3613-3p expression was analyzed by RT-qPCR, and the results verified that miR-3613-3p expression was reduced in HS-treated HUVECs compared with control cells (P<0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous miRNA microarray analysis, miR-3613-3p expression levels were decreased in HUVECs under heat stress (19). To confirm the downregulation of miR-3613-3p in heat-treated cells, miR-3613-3p expression was analyzed by RT-qPCR, and the results verified that miR-3613-3p expression was reduced in HS-treated HUVECs compared with control cells (P<0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, miRNA (miR)-155, miR-320, miR-222, miR-125b, miR-410 and miR-218 have been reported to regulate adherens junction disassembly responses, cell migration and cell morphology, contributing to changes in the permeability and integrity of the vasculature (1618). As underlying regulatory mechanisms such as miRNA expression in response to HS were unknown, miRNA expression was analyzed in our previous study via miRNA microarrays; it was demonstrated that heat stress altered miRNA expression in HUVECs, with 31 miRNAs differing significantly in expression between HUVECs exposed to severe heat treatment and untreated control cells (20 miRNAs were downregulated and miRNAs were 11 upregulated) (19). Only 1% of the human miRNA assemblage (31/3,100) exhibited differential expression following heat treatment, indicating that the regulatory activity of heat stress may be specific toward a subset of miRNAs in HUVECs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation-related gene expression in the brain can be regulated not only by transcription factors at the transcriptional level but also by miRNAs at the post-transcriptional level. Many miRNAs play an important role in heat-related disease (Roufayel et al, 2014; Liu et al, 2017). Given that miR-155 is upregulated by heat stress in peripheral blood mononuclear cells, as shown by deep sequence data analysis (Sengar et al, 2018), and participates in the proinflammatory responses (Faraoni et al, 2009), we hypothesized that miR-155 was deeply involved in regulating heat stress-induced microglial activation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed in triplicate. Relative miRNA expression was calculated on the basis of the C T method where C T values of individual miRNA data were normalized to C T values of U6 snRNA as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%